STRATEGI KOMUNIKASI BOX2BOX MEDIA NETWORK DALAM PERSAINGAN INDUSTRI PODCAST DI INDONESIA - Muhammad Fazri Candra; Zahra Nabila Azka (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
Abstract The audio-based media industry is always growing, one of which is the existence of broadcasts or better known as podcasts. The great interest of listeners from siniar has made the industry grow, one of which is the birth of Box2box Media Network, which is a podcast-based media network. This research discusses the Box2Box Network communication strategy in the Podcast Industry Competition. This study uses descriptive qualitative research methods with data collection carried out using interviews, observation, and documentation.This research uses communication aspects, namely audience introduction, message preparation, method determination, media determination. The results of the communication strategy research conducted in Box2Box is by creating a business model that is carried out in Box2Bx, one of which is brand placement, which covers various possibilities, beyond that social media as part of a vertical podcast, selling podcasters as talent, access and connection to resources, whether it's talent, editors, or designers or other figures, who open up opportunities for collaboration and can advance the quality of Box2Box Media Network.